Nursing Care Satisfaction and Readiness for Hospital Discharge States of Patients Hospitalized in Internal Medicine Clinics: Descriptive Cross-sectional Research Example - Turan, Gülcan Bahçecioğlu; Özer, Zülfünaz; Atan, Gülden (My University, 2021)
Objective: This descriptive and cross-sectional study \rwas conducted to evaluate the nursing care satisfaction and readiness \rfor hospital discharge of patients hospitalized in internal medicine \rclinics. Material and Methods: The universe of this study consisted \rof patients treated in the internal clinics of Atatürk University hospital between May and September 2019. The sample of the study, on \rthe other hand, consisted of 372 patients aged 18 and over who did not \rhave hearing, vision and mental problems, voluntarily accepted to \rparticipate in the study, had cognitive competence to answer the questions. The data were collected by using “personal information form”, \r“Newcastle Nursing Care Satisfaction Scale”, and “Readiness for \rHospital Discharge Scale”. Results: It was found that average age of \rthe patients in the study was 58.7±17.5 years; 50.8% were male, \r29.8% were illiterate, 90.6% were married, 78.5% had a moderate \rlevel of income, 59.4% were hospitalized from the outpatient clinics \rand 70.7% were very satisfied with nursing care. Average nursing care \rsatisfaction of the patients was found to be 88.23±12.5. Readiness for \rhospital discharge total score of the patients was 6±1.99 and the highest score was taken from expected support sub-dimension \r(9.05±1.83), while the lowest score was taken from knowledge \r(4.18±4.15) sub-dimension. A statistically significant inverse relationship was found between the age and number of hospitalizations of \rthe patients and the total score of the Readiness for Hospital Discharge Scale, personal care and coping skills sub-dimension scores \r(p<0.05). Conclusion: It was found that the patients had high nursing \rcare satisfaction levels and that they were not sufficiently ready for \rdischarge.
Keywords: Genel ve Dahili Tıp; Sağlık Bilimleri ve Hizmetleri; Hemşirelik